Loneliness in Haruki Murakami’s After Dark (2007): A Focalization Analysis - Linna Amanda (Universitas Pendidikan Indonesia (UPI), 2019)
Young adult literature provides varieties of themes and concepts of life for teenager to explore. After Dark by Haruki Murakami (2007) focuses on abstract concepts of loneliness. This study attempts to analyze how are the forms of loneliness depicted in the novel through the main character, Mari Asai, by scrutinizing the literary tool of focalization (Bal, 1985). Mijuskovic’s theory (2014) that distinguishes four forms of loneliness and three ways to overcome loneliness are also used in this study. Mari Asai’s loneliness is found to be a complex four forms of loneliness that she experiences throughout her life: aloneness, loneliness, isolation, and alienation. The forms are based on some sources and ways to overcome loneliness that she reveals and finds throughout the story. Mari’s loneliness is overcome when she is willing to have conversations with others, build relationships, and seek solitude within herself. From the focalization used in the novel, the loneliness is mostly shown through Character-Bound Focalization on the second level (CF2). CF2 is found to be the most useful type of focalization that helps to depict what the main character think and feel because of its detailed use. Mari Asai’s experience of loneliness shows how loneliness is a common and important thing for young people to progress into adulthood. Through the whole progress of the main character coping with her loneliness, the novel provides guidance for young adult to go through loneliness as a stage that may happen in life. Keywords: character, focalization, forms, loneliness, young adult literature